Failure mode, effects and criticality analysis of dragline components and evaluation of risk priority number for effective maintenance planning - Sahu A.R.; Palei S.K. (My University, 2025)
The occurrences of unexpected failures in heavy earthmoving machines (HEMMs) lead to the downtime that reduces the productivity, safety, and reliability of the machines. Unwanted failures increase the likelihood of unplanned maintenance activities. Dragline is an HEMM used in the opencast coal mines for removal of the overburden and its failure is undesirable as the capital invested on draglines are very high. This paper utilises the failure mode, effects and criticality analysis (FMECA) to identify the critical failure components of the dragline system and their root causes. Seven subsystems and thirty components for failure have been identified in the two-year maintenance record 2014-16 of dragline. Risk estimation has been carried out for the dragline components to estimate the risk priority number (RPN) considering four factors: failure occurrence, production loss, degradation in performance, and detectability. The RPN is used to categorise the components into three groups: high, medium, and low risk components. Based on the risk groups of component, the inspection interval and inspection time can be optimised to avoid the unexpected failure of the component and eventually improving the productivity of the dragline system. © 2020, Books and Journals Private Ltd.. All rights reserved.